Angular Dependence of the Magnetic Properties of Permalloy Nanowire Arrays: A Comparative Analysis Between Experiment and Simulation - Escrig-Murua, J (Elsevier B.V., 2020)
This work contributes to the understanding of angular dependence of the magnetic properties of Permalloy nanowire arrays by means of a comparative analysis between experiment and micromagnetic simulations. On the one hand, Permalloy nanowires of 30 nm in diameter and 1 μm in length were synthesized by AC electrodeposition inside mesoporous alumina templates. Magnetic experimental measurements show that both coercivity and remanence decrease monotonously as the angle, at which the external field is applied, increases. On the other hand, the comparison between the simulation of a nanowire array and that performed for one single nanowire reveals that the magnetostatic interactions between the nanowires strongly modifies not only the shape of the hysteresis curve but also the coercivity and remanence values. Besides, simulations also disclose that the nanowires reverse their magnetization through the nucleation and propagation of transverse domain walls. Moreover, the simulation of an array of nanowires also discloses that the hysteresis curve exhibits noticeable jumps in the magnetization that are proportional to the number of nanowires that reverse their magnetization in the array. This latter could provide an interesting hint to control the performance of magnetic nanodevices. © 2019 Elsevier B.V.
Keywords: Magnetic reversal mechanisms; Permalloy nanowire array; Micromagnetic simulations